2021
DOI: 10.1371/journal.pone.0256783
|View full text |Cite
|
Sign up to set email alerts
|

3D modelling of drug-coated balloons for the treatment of calcified superficial femoral arteries

Abstract: Background/Objectives Drug-coated balloon therapy for diseased superficial femoral arteries remains controversial. Despite its clinical relevance, only a few computational studies based on simplistic two-dimensional models have been proposed to investigate this endovascular therapy to date. This work addresses the aforementioned limitation by analyzing the drug transport and kinetics occurring during drug-coated balloon deployment in a three-dimensional geometry. Methods An idealized three-dimensional model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“… 21 Additionally, Kolandaivelu et al presented a supervised machine learning framework, using drug coated balloons as an exemplary scenario (Figure 6 ), to process data generated from coarse meshes to predict results derived from highly‐refined meshes – thereby drastically increasing the efficiency in the computational modeling workflow. 69 However, it must be noted that all the studies to‐date, except one, 70 are inherently limited by the fact that the geometric domain is simplified down to a one‐ or two‐dimensional representation. While it has been shown that lower‐dimensional models can adequately predict the numerical results that would be derived from three‐dimensional models when the device‐vessel interface is spatially uniform, the assumption begins to break down as heterogeneity in both the vessel tissue and balloon surface are incorporated into the computational model.…”
Section: Biophysics‐based Design Considerations and Strategiesmentioning
confidence: 99%
“… 21 Additionally, Kolandaivelu et al presented a supervised machine learning framework, using drug coated balloons as an exemplary scenario (Figure 6 ), to process data generated from coarse meshes to predict results derived from highly‐refined meshes – thereby drastically increasing the efficiency in the computational modeling workflow. 69 However, it must be noted that all the studies to‐date, except one, 70 are inherently limited by the fact that the geometric domain is simplified down to a one‐ or two‐dimensional representation. While it has been shown that lower‐dimensional models can adequately predict the numerical results that would be derived from three‐dimensional models when the device‐vessel interface is spatially uniform, the assumption begins to break down as heterogeneity in both the vessel tissue and balloon surface are incorporated into the computational model.…”
Section: Biophysics‐based Design Considerations and Strategiesmentioning
confidence: 99%
“…Consider the process of endovascular drug delivery by a drug-coated balloon adhered to the luminal wall of an artery for a short duration, typically 60-120 seconds in practice [9,11].…”
Section: Problem Definitionmentioning
confidence: 99%
“…Numerical studies are typically computationally expensive and make a number of (different) assumptions to enable solutions to be obtained in a reasonable time frame. Drug delivery from the DCB is typically modeled as either a constant concentration for a finite time [11] or a timedependent flux [6][7][8][9][10]. All of the aforementioned numerical models assume that drug is transported through the arterial wall due to diffusion: only two models [8,9] account for advective transport due to the known pressure gradient across the arterial wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PAD affects people aged 25 years and over. Recent data indicated that about 202 million people have this disease, while the number increased to 230 million people infected in 2015 [1]. As a result, powerful computational tools have been developed as a result of the PAD study's widespread interest.…”
Section: Introductionmentioning
confidence: 99%